2003
DOI: 10.1002/mrd.10267
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis during spermatogenesis in the spotted ray Torpedo marmorata

Abstract: This article is a cytological and molecular investigation on the occurrence of apoptosis during spermatogenesis in Torpedo, a cartilaginous fish characterised by a typical cystic testis. Using DNA fragmentation and Bak gene expression, it demonstrated that germ cells undergo apoptosis only at the stages of spermatocyte and spermatid, and degeneration also involves Sertoli but not Leydig cells. In immature cysts, this cellular process probably occurs when the ratio of germ cells to the only Sertoli cell (SC) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 44 publications
1
18
1
Order By: Relevance
“…McClusky, unpublished observations). Our findings, however, differ from those reported in the spotted ray, Torpedo marmorata, which show no stage-dependency and cell-type specificity of testicular apoptosis (Prisco et al 2003). Since a ZD has also been noted in each testicular lobe of the Atlantic stingray, Dasyatis sabina (Maruska et al 1996), and a ZD and stage-dependent premeiotic apoptosis seen in the little skate, Raja erinacea (L.M.…”
Section: Discussioncontrasting
confidence: 99%
“…McClusky, unpublished observations). Our findings, however, differ from those reported in the spotted ray, Torpedo marmorata, which show no stage-dependency and cell-type specificity of testicular apoptosis (Prisco et al 2003). Since a ZD has also been noted in each testicular lobe of the Atlantic stingray, Dasyatis sabina (Maruska et al 1996), and a ZD and stage-dependent premeiotic apoptosis seen in the little skate, Raja erinacea (L.M.…”
Section: Discussioncontrasting
confidence: 99%
“…At the time of cell division, it was observed that within the same spermatocyst, there were spermatoblasts containing cells at different phases of cell division, thus resulting in the presence of different cell types within the same spermatocyst, with the presence of secondary spermatocytes and some spermatoblasts and spermatids within others. Prisco et al (2003) also identified different stages of cell differentiation in the same spermatogenic cyst in Torpedo marmorata and also among other elasmobranchs, such as Centroscymnus coelolepis and Centrophorus squamosus (Girard et al, 2000).…”
Section: Discussionmentioning
confidence: 72%
“…BPA is widely found in aquatic environments and causes reproductive toxicity in fish, often resulting in abnormal testicular and ovarian development [16][17][18]28,29]. BPA has also been demonstrated to accumulate in various fish tissues, leading to pathological changes, including changes in the endocannabinoid system, changes in the ontogeny of the cortisol stress response, and energetic impairments [22,23,30].…”
Section: Discussionmentioning
confidence: 99%
“…Fish are often used to evaluate the health of aquatic ecosystems, in particular, physiological and biochemical changes in fish are considered biomarkers of environmental pollution [15]. Previous studies have suggested that BPA, as an analog of estrogen, may exert an estrogenic effect on fish gonad development and reproductive axis-related gene expression [16][17][18][19][20]. BPA also affects various biological processes in fish, including metabolism, individual cortisol stress responses, energy metabolism, muscle structure, motor behavior, and axonal growth, thereby affecting fish growth and development [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%